2014
DOI: 10.1097/sla.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Occurrence of Preneoplastic Lesions and Accumulation of Loss of Heterozygosity in Patients With Gallbladder Stones Suggest Causal Association With Gallbladder Cancer

Abstract: Patients with gallstones had a high frequency of preneoplastic lesions and accumulation of LOH at various tumor suppressor genes, suggesting a possible causal association of gallstones with GBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 23 publications
1
38
0
2
Order By: Relevance
“…However, a poor overlap exists between these biomarkers of gallbladder cancer. Thus, it might be a better resolution to establish more-accurate prognostic gene signatures by using a combination of different types of transcripts (24). A growing volume of literature has demonstrated that noncoding RNAs, predominantly miRNAs, could serve as potential biomarkers of gallbladder cancer (3,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, a poor overlap exists between these biomarkers of gallbladder cancer. Thus, it might be a better resolution to establish more-accurate prognostic gene signatures by using a combination of different types of transcripts (24). A growing volume of literature has demonstrated that noncoding RNAs, predominantly miRNAs, could serve as potential biomarkers of gallbladder cancer (3,25).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the TP53 gene, either by deletion or mutation, is the most common genetic alteration observed across cancers at different anatomic sites [23], including GBC [24,25]. TP53 alterations are observed even in histologically normal epithelia from GDS patients with chronic cholecystitis, and the frequency of TP53 alterations increases as impairment of epithelial architecture progresses from metaplasia to invasive carcinoma [26,27]. Environmental exposures can lead to TP53 mutations and affect inflammatory and other immune responses.…”
Section: Inflammation and Cancermentioning
confidence: 99%
“…In a study by Jain and colleagues, the authors examined 350 gallbladder specimens from patients with gallstones, and found mucosal hyperplasia in 32%, metaplasia in 47.8%, dysplasia in 15.7%, and carcinoma in situ in 0.6% of specimens. 11 The authors were able to show loss of genetic heterozygosity in 2.1% to 47.8% of preneoplastic lesions at 8 different loci for several tumor suppressor genes associated with gallbladder cancer, but showed no loss of heterozygosity in normal gallbladders, thereby suggesting a possible mechanistic association between gallstones and gallbladder cancer beyond inflammation and neoplasia.…”
Section: Etiology and Pathogenesismentioning
confidence: 96%